Incorporation of Sustainability in Traditional Architecture: a Narrative Review - Hadi, M. Syamsul; Wahjutami, Erlina Laksmiani; Tutuko, Pindo (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study conducts a narrative review to explore the integration of sustainability principles into traditional architecture, a field that has garnered significant attention amid global sustainability challenges. Traditional architecture, with its use of locally sourced materials and climate-responsive designs, inherently supports sustainability by minimizing environmental impact and energy consumption. Using VOSviewer software, this study analyzes 50 research articles from the SciSpace platform (Typeset.io), identifying key thematic clusters related to traditional architecture, vernacular design, and energy efficiency. The results reveal that traditional building practices, particularly those using natural ventilation and eco-friendly materials, offer valuable insights for modern sustainable architecture. This analysis also highlights a trend toward incorporating traditional architectural wisdom into contemporary practices, particularly as the urgency to address climate change intensifies. By mapping research patterns and key concepts, this study provides a comprehensive overview of how traditional architecture can inspire innovative, sustainable design solutions in contemporary architectural practices, making significant contributions to the field. This research aims to fill the gap in the literature by providing a comprehensive study that maps the integration of sustainability practices in traditional architecture, which is currently limited. The findings are expected to offer new insights into how the concept of sustainability can be applied in traditional architecture and innovated in modern architectural practices.